The Effects of Excitatory and Inhibitory Social Cues on Cocaine-Seeking Behavior - Smith, Mark A.; Zhang, Huailin; Robinson, Andrea M. (Frontiers in Behavioral Neuroscience, 2016)
Social partners influence the likelihood of using drugs, developing a substance use disorder, and relapse to drug use after a period of abstinence. Preclinical studies report that social cues influence the acquisition of cocaine use, the escalation of cocaine use over time, and the compulsive patterns of cocaine use that emerge during an extended binge. The purpose of this study was to examine the effects of social cues on the reinstatement of cocaine-seeking behavior after a period of abstinence. Male rats were obtained at weaning, assigned to triads (3 rats/cage), reared to adulthood, and implanted with intravenous catheters. Rats from each triad were then assigned to one of three conditions: (1) test rats were trained to self-administer cocaine and were tested for reinstatement, (2) cocaine partners were trained to self-administer cocaine and were predictive of response-contingent cocaine delivery, and (3) abstinent partners were not given access to cocaine and were predictive of extinction. Test rats alternated social partners every 5 days for 20 days such that responding was reinforced with cocaine in the presence of the cocaine partner (S+) for 10 days and not reinforced with cocaine in the presence of the abstinent partner (S-) for 10 days. Responding of the test rats was then extinguished over 7 days under isolated conditions. Tests of reinstatement were then conducted in the presence of the cocaine partner and abstinent partner under extinction conditions. Neither social partner reinstated responding relative to that observed on the final day of extinction; however, responding was greater in the presence of the cocaine partner (S+) than the abstinent partner (S-) during the reinstatement test. These data fail to demonstrate that a social partner reinstates cocaine-seeking behavior after a period of abstinence, but they do indicate that social partners can serve as either excitatory or inhibitory discriminative stimuli to influence drug-seeking responses.